Why are people more pro-trade than pro-migration? - Anna Maria Mayda (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2006)
I analyze individual attitudes towards trade and immigration in comparative terms. I find that individuals are on average more pro-trade than pro-immigration across several countries. I identify a key source of this di.erence: the cleavage in trade preferences, absent in immigration attitudes, between individuals working in traded as opposed to non-traded sectors.
Keywords: F22; F1; J61; 330; Immigration Attitudes; Trade Attitudes; Political Economy